Two-dimensional chiral molecular assembly on solid surfaces: formation and regulation. Issue 2 (25th March 2015) - Chen, Ting; Wang, Dong; Wan, Li-Jun
Abstract: The expression of chirality in 2D molecular assemblies on solid surfaces has unique features compared to the analogous process in 1D and 3D supramolecular assemblies. Understanding the formation of chiral molecular assemblies on surfaces not only provides insight into the origin and transfer of chirality in many enantioselective processes, but also aids rational design and construction of chiral architectures and materials. This present contribution reviews recent studies on how chirality is induced and expressed on the surface at different levels, both from intrinsically chiral and achiral molecules. Furthermore, we discuss the regulation effect of some pivotal factors, for example, the chemical structure, the chiral auxiliary molecules, and the assembled environments, on the expression of chirality in molecular assembly.